2018
DOI: 10.1159/000487885
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <b><i>Allium cepa</i></b> Extract on Lung Oxidant, Antioxidant, and Immunological Biomarkers in Ovalbumin-Sensitized Rats

Abstract: Objectives: To evaluate the effects of Allium cepa (A. cepa) on levels of oxidants, antioxidants, and immunological markers in bronchoalveolar lavage fluids (BALF) of sensitized rats. Materials and Methods: Oxidant/antioxidant markers and cytokines in BALF of control rats treated with saline (group C), ovalbumin-sensitized rats (group S), rats treated with 1.25 μg/mL dexamethasone and 3 doses of A. cepa extract (35, 70, and 140 mg/kg body weight [BW]/day) (S + AC) were investigated. Comparison of the results b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Previous studies have reported that oxidative stress markers such as NO 2 , NO 3 , and MDA were amplified, whereas SOD, catalase, IFN‐γ were found declined in the asthmatic animals when compared with normal control group. In contrast, the total white blood corpuscles (WBC count), NO 2 and NO 3 were found significantly reduced in the dexamethasone and plant extract treated asthmatic groups (Marefati et al, ; Shakeri, Soukhtanloo, & Boskabady, ). Ceylan et al () reported that MDA levels were significantly higher and glutathione levels were lower in the blood plasma of asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that oxidative stress markers such as NO 2 , NO 3 , and MDA were amplified, whereas SOD, catalase, IFN‐γ were found declined in the asthmatic animals when compared with normal control group. In contrast, the total white blood corpuscles (WBC count), NO 2 and NO 3 were found significantly reduced in the dexamethasone and plant extract treated asthmatic groups (Marefati et al, ; Shakeri, Soukhtanloo, & Boskabady, ). Ceylan et al () reported that MDA levels were significantly higher and glutathione levels were lower in the blood plasma of asthmatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory disease that weakens the airways in lungs and hinders breathing. Vigorous inductions of inflammatory cells, excessive mucus generation, airway narrowing, and bronchial hyper reactivity are the major mediators of asthma (Marefati et al, ). Similar to autoimmune diseases, asthmatic response also involves a wide range of immune cells including mast cells, eosinophils, neutrophils, airway epithelial cells, smooth muscle cells, and T‐lymphocytes (Gao, Ying, & Dai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Allium cepa L. (Family Amaryllidaceae) is one of the most commonly consumed vegetables and has also been used for medicinal purposes for numerous ailments such as ulcer wounds, scars, dysentery, inflammation, hypertension and also in respiratory conditions such as cough, asthma, and bronchitis ( Lanzotti, 2006 ; Upadhyay, 2016 ; Zeng et al, 2017 ). Onion bulb extract (OBE) has also been shown to effectively reduce airway inflammation, IL4, and IgE levels and induces oxidation in animal models of asthma ( Oliveira et al, 2015 ; Marefati et al, 2018 ). Thiosulfinates (TS) and cepaenes (CS), isolated from onions and/or synthesized, were also shown to have dose-dependent inhibitory effects on both cyclooxygenase and 5-lipoxygenase activity ( Dorsch et al, 1990 ; Wagner et al, 1990 ) and inhibit in vitro chemotaxis of human granulocytes induced by formyl-methionine-leucine-phenylalanine (WKYMvm) ( Dorsch et al, 1990 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cells elevated in BAL fluid are also source of leukotrienes that are formed by the breakdown of a membrane constituent, arachidonic acid, via the 5-lipoxygenase enzyme pathway. Leukotrienes may a play an important role in attracting neutrophils and eosinophils into airways, and produce P a g e / S a y f a 64 bronchoconstriction, mucus secretion, microvascular leakage, airway edema, and neuronal interactions [14,17,[26][27][28]. Therefore, the reduction of leukocyte infiltration may be a mechanism for the beneficial effect of TQ.…”
Section: Discussionmentioning
confidence: 99%